Patients with HCV Genotype-1 who have Failed a Direct-Acting Antiviral Regimen: Virological Characteristics and Efficacy of Retreatment. Issue 7 (October 2019) - Pisaturo, Mariantonietta; Starace, Mario; Minichini, Carmine; De Pascalis, Stefania; Macera, Margherita; Occhiello, Laura; Messina, Vincenzo; Sangiovanni, Vincenzo; Claar, Ernesto; Precone, Davide; Stornaiuolo, Gianfranca; Stanzione, Maria; et al.
Background: This real-world clinical setting study characterized the virological patterns in genotype-1 patients failing interferon (IFN)-free regimens and evaluated the efficacy of re-treatment. Methods: A total of 73 consecutive patients failing IFN-free regimens were enrolled (17 genotype-1a and 56 −1b). At failure Sanger sequencing of NS3, NS5A and NS5B regions was performed by home-made protocols. Results: In patients having failed an NS3 inhibitor, the prevalence of NS3-RASs was higher in the 10 with genotype-1a than in the 24 with genotype-1b (80% versus 41.6%). In patients treated with an NS5A inhibitor, the prevalence of NS5A-RASs was very high in the 14 with genotype-1a and the 27 with genotype-1b (78.6% and 92.5%, respectively). In patients having failed sofosbuvir, the prevalence of NS5B-RASs was more frequently identified in the 45 with genotype-1b than in the 10 with genotype-1a (37.7% versus 10%). The prevalence of NS5B-RASs in patients having failed dasabuvir was high in both genotypes, 66.6% in the 6 with genotype-1a and 45.5% in the 11 with genotype-1b. The 6 patients re-treated with genotype-1a less frequently (50%) showed sustained virological response (SVR) than the 18 with genotype-1b (88.8%; P =0.07). SVR was more frequent in the 21 patients with an effective second-line direct-acting antiviral (DAA) regimen than the 3 without (90.4% versus 0%; P <0.005). Conclusions: The prevalence of RASs was high in our real-world population. NS3, NS5A and NS5B sequencing seems mandatory in the choice of DAA re-treatment.